Sodium citrate ingestion enhances 30 km cycling performance - Potteiger, J. A.; Nickel, G. L.; Webster, M. J.; Haub, M. D.; Palmer, R. J. (International Journal of Sports Medicine, 1996)
The purpose of this study was to examine the effects of sodium citrate (CIT) ingestion on 30 km cycling performance. Eight trained male cyclists (VO2max = 54.7 +/- 1.7 ml.kg-1.min-1) performed two 30 km cycling time trials. The trials were double blind and randomly assigned from CIT or placebo (PLC), with both dosages at 0.5 g.kg body wt-1. Blood samples were collected from an indwelling catheter at 10 km intervals and analyzed for PO2, PCO2, pH, and lactate concentration ([La]). Power output, heart rate (HR) and RPE were measured at 5 min intervals during the trials, while cycling performance was determined from time to complete the 30 km. A repeated measures ANOVA and dependent t-tests were used to locate differences between the trials. A significant difference (p < or = 0.01) was observed for pH and [La] during the trials with CIT being elevated above PLC throughout the ride. No significant differences (p > 0.01) were observed for any of the other dependent variables. However, power output and HR were slightly elevated during the CIT trial. Performance time was significantly faster (p < or = 0.05) for the CIT trial (3459.6 +/- 97.4 s) compared to the PLC trial (3562.3 +/- 108.5 s). The data indicate that favorable metabolic conditions were obtained following CIT ingestion and these likely contributed to the improvement in cycling performance.